Mobilizing effort in complex motor tasks: Try-harder instructions in deceptive actions - Böer, Nils Tobias; Steinborn, Michael B.; Weigelt, Matthias; Güldenpenning, Iris (Psychology of Sport and Exercise)
This study investigated whether external effort mobilization through try-harder instructions enhances performance in complex motor tasks, as reflected by the reduction of costs associated with producing a deceptive action. Basketball passing movements with and without head fakes were examined in a reaction-time paradigm. Participants were generally instructed to initiate the movement as fast and accurately as possible, while try-harder instructions were presented in 25 % of trials, prompting participants to mobilize all their cognitive resources to perform even faster. To investigate if athletic expertise modulates the potential effects of effort mobilization, basketball novices and experienced players were tested. Results demonstrated that try-harder instructions generally improved participants’ performance, facilitating faster response initiation times and movement execution, as well as a specific reduction in initiation time variability. Novices benefited more than experienced players, indicating that effort results in greater improvement when complex motor actions (for example, passes with head fakes) are not yet fully stabilized and lack automated fluency. This pattern suggests that effort enhances performance in complex actions when performance is limited by the amount of cognitive capacity available, supporting the coordination of partly conflicting movement components within tight temporal constraints. The findings extend previous research on effort mobilization from simple to complex motor tasks. Try-harder instructions appear to enhance performance primarily by reducing attentional lapses rather than generally improving processing speed. Future research should investigate the effectiveness of effort mobilization in experienced athletes in situations of high concurrent cognitive load.
Keywords: Effort; Try-harder instruction; Deception; Basketball; Head fake; Fake production

Creating Synthetic Training Datasets for Inspection in Machine Vision Quality Gates in Manufacturing - Gräßler, Iris; Hieb, Michael (Lectures)
Manufacturing companies face the challenge of reaching required quality standards. Using optical sensors and deep learning might help. However, training deep learning algorithms require large amounts of visual training data. Using domain randomization to generate synthetic image data can alleviate this bottleneck. This paper presents the application of synthetic image training data for optical quality inspections using visual sensor technology. The results show synthetically generated training data are appropriate for visual quality inspections.
Keywords: synthetic training data; machine vision quality gates; deep learning; automated inspection and quality control; production control

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology

Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

Re-Envisioning Industrial Control Systems Security by Considering Human Factors as a Core Element of Defense-in-Depth - Pottebaum, Jens; Rossel, Jost; Somorovsky, Juraj; Acar, Yasemin; Fahr, René; Arias Cabarcos, Patricia; Bodden, Eric; Gräßler, Iris (2023 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW))
The security of Industrial Control Systems is relevant both for reliable production system operations and for high-quality throughput in terms of manufactured products. Security measures are designed, operated and maintained by different roles along product and production system lifecycles. Defense-in-Depth as a paradigm builds upon the assumption that breaches are unavoidable. The paper at hand provides an analysis of roles, corresponding Human Factors and their relevance for data theft and sabotage attacks. The resulting taxonomy is reflected by an example related to Additive Manufacturing. The results assist in both designing and redesigning Industrial Control System as part of an entire production system so that Defense-in-Depth with regard to Human Factors is built in by design.
Keywords: Defense-in-Depth; Human Factors; Production Engineering; Product Design; Systems Engineering

Co-Evolutionary Diversity Optimisation for the Traveling Thief Problem - Nikfarjam, Adel; Neumann, Aneta; Bossek, Jakob; Neumann, Frank (Parallel Problem Solving from Nature (PPSN XVII))
Recently different evolutionary computation approaches have been developed that generate sets of high quality diverse solutions for a given optimisation problem. Many studies have considered diversity 1) as a mean to explore niches in behavioural space (quality diversity) or 2) to increase the structural differences of solutions (evolutionary diversity optimisation). In this study, we introduce a co-evolutionary algorithm to simultaneously explore the two spaces for the multi-component traveling thief problem. The results show the capability of the co-evolutionary algorithm to achieve significantly higher diversity compared to the baseline evolutionary diversity algorithms from the literature.
Keywords: Co-evolutionary algorithms; Evolutionary diversity optimisation; Quality diversity; Traveling thief problem

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

V-model based development of cyber-physical systems and cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel; Thiele, Henrik (Procedia CIRP)
Challenges of the development of mechatronic systems and corresponding production systems have increased steadily. Changes are primarily due to increased product complexity and the connection to the internet of things and services, enabling Cyber-Physical Systems (CPS) and Cyber-Physical Production Systems (CPPS). Major innovations of the revised VDI guideline 2206 for developing mechatronic systems are systems thinking as a core element and six checkpoints for structuring deliverables along the V-Model. These checkpoints serve for orientation in result progress and thus enable a structured and complete development process. However, tasks and checkpoints of the new guideline focus on the product development itself without integrating the development of related CPPS, enabling optimization simultaneously to system development. Implications are derived by a three-step analysis. The paper at hand contributes fundamental extensions of the checkpoint questions regarding integrated CPPS development. These questions provide methodical support for system developers of CPPS for CPS by enabling the project manager to check the status, schedule further development steps and evaluate the maturity of the whole, integrated development.
Keywords: Cyber-Physical Production System (CPPS); V-Model; Product System Development; Integrated Development; VDI 2206

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Experimentelle Untersuchung einse modifzierten Nasspressverfahrens für die Herstellung von hybriden Metall-Faserverbundkunststoff-Bauteilen - Opdemom, Hermann
Das Nasspressverfahren ist ein Serienherstellungsprozess für Bauteile aus duroplastischen Faserverbundkunststoffen (FVK) mit einer geringen Geometriekomplexität. Im Rahmen dieser Arbeit wurde ein modiﬁziertes Nasspressverfahren untersucht, welches die Herstellung von hybriden Blech-FVK-Strukturen ermöglicht. Die stoffschlüssige Verbindung zwischen dem metallischen Trägerbauteil und einem lokalen FVK-Verstärkungselement wird durch Co-Bonding im Nasspresswerkzeug aufgebaut. Epoxidbasierte Matrixharze und Klebstoffe wurden mit Methoden der Klebtechnik sowie thermischen und rheometrischen Prüfungen charakterisiert, um ein materialspeziﬁsches Fertigungsprozessfenster einzugrenzen. Experimentelle Untersuchungen zum Nasspressen von GFK-Laminaten und Stahl-GFK-Hybridstrukturen fokussierten die Mikrostruktur und das strukturelle Verhalten von stoffschlüssigen Hybridverbindungen. Unter anderem wurden Einﬂüsse von zeit-, temperatur- und druckabhängigen Fertigungsparametern sowie der Einsatz von Strukturklebstoffﬁlmen und internen Trennmitteln analysiert. Anhand von Fallturmtests an hybriden Demonstratorkomponenten konnte das modiﬁzierte Nasspressverfahren für die Herstellung crashrelevanter Karosseriebauteile qualiﬁziert werden.
Keywords: Leichtbau; Faserverbundkunststoffe; Nasspressverfahren; Hybridbauteile; Rheologie; Klebtechnik; Co-Bonding

Insights into the reaction mechanism and particle size effects of CO oxidation over supported Pt nanoparticle catalysts - Neumann, Sarah; Gutmann, Torsten; Buntkowsky, Gerd; Paul, Stephen; Thiele, Greg; Sievers, Heiko; Bäumer, Marcus; Kunz, Sebastian (Journal of Catalysis)
CO oxidation is an extensively studied reaction in heterogeneous catalysis due to its seeming simplicity and its great importance for emission control. However, the role of particle size and more specifically structure sensitivity in this reaction is still controversial. In the present study, colloidal “surfactant-free” Pt nanoparticles (NPs) in a size regime of 1–4 nm with narrow size distribution and control over particle size were synthesized and subsequently supported on Al2O3 to prepare model catalysts. CO oxidation was performed using Pt NPs catalysts with particles sizes of 1, 2, 3, and 4 nm at different reaction temperatures. It is shown that the reaction exhibits a particle size effect that depends strongly on the reaction conditions. At 170 °C, the reaction seems to proceed within the same kinetic regime for all particle sizes, but the surface normalized activity depends strongly on the particle size, with maximum activity for nanoparticles 2 nm in diameter. A temperature increase to 200 °C leads to a change of the kinetic regime that depends on the particle size. For Pt NPs 1 nm in diameter a reaction order of 1 for O2 was observed, indicating that O2 adsorbs molecularly and dissociates in a following step, which represents the generally accepted mechanism on Pt surfaces. The reaction order of −1 for CO demonstrates that the surface is saturated with CO under reaction conditions. With increasing particle size, the reaction orders of O2 and CO change. For particles 2 nm in size, an increase in temperature also results in reaction orders of 1 for O2 and −1 for CO; NPs of 3 and 4 nm, even at higher temperatures, show no clear kinetic behavior that can be explained by a single reaction mechanism. Instead, the Boudouard reaction between two adjacent adsorbed CO molecules was identified as an important additional reaction pathway that occurs preferentially on large particles and causes more complex kinetics.
Keywords: Solid state NMR; “Surfactant-free” platinum nanoparticles; CO oxidation; Particle size effect; Structure sensitivity

Light-responsive nanoparticles based on new polycarbonate polymers as innovative drug delivery systems for photosensitizers in PDT - Anderski, Juliane; Mahlert, Laura; Sun, Jingjiang; Birnbaum, Wolfgang; Mulac, Dennis; Schreiber, Sebastian; Herrmann, Fabian; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)
Keywords: NanoparticlesLight-responsive polymersPhotodynamic therapyPoly(lactic-co-glycolic acid)Intestinal cancer

MEDIA ENGINEERING WITH A CONTENT HUB SYSTEM. GENERIC CONTENT TRANSFORMATION FOR MOBILE MEDIA - Herzog, Michael; Trier, Matthias (International Journal of Computing)
A primary problem in multimedia content production is the plethora of formats and the resulting multiple point-to-point transformation processes in different content formatting specifications. However, these content transformation processes can be conceptually broken down into a limited set of abstract principles. This allows a unified approach that theoretically enables the transformation of any given input channel into any desired output. Based on this principle, the present article introduces the concept of Generic Content Transformation and the related project MOCCA, which develops the corresponding software implementation of generic content transformation for a variety of input and output channels. To balance technical similarities with specific properties of different media channels, we suggest a combination of an XML-based structure (MocML) and a high level authoring environment. Generic Content Transformation further allows for novel means of accessing assets via compound search algorithms. In the second part we summarize and discuss current results and experiences in three scenarios of media production, including mobile media.
Keywords: Multimedia Authoring; Mobile Content; Cross Media Production; Content Engineering; Media Retrieval

Studying the Co-Construction of Interaction Protocols in Collaborative Tasks with Humans - Vollmer, Anna-Lisa; Grizou, Jonathan; Lopes, Manuel; Rohlfing, Katharina; Oudeyer, Pierre-Yves (2014 Joint IEEE International Conference on Development and Learning and on Epigenetic Robotics)
Keywords: interaction; communication; co-construction; interaction protocols

Eine Inklusion unterstützende Didaktik – Rekonstruktionen aus der Perspektive inklusionserfahrener Lehrkräfte - Textor, Annette; Kullmann, Harry; Lütje-Klose, Birgit (Jahrbuch für Allgemeine Didaktik)
Im Zuge der systemweiten Einführung schulischer Inklusion gewinnen Ansätze einer Inklusion unterstützenden Didaktik zunehmend an Bedeutung. Der Beitrag beschreibt zunächst ausgehend vom Inklusionsbegriff die fünf Leitlinien des Bielefelder Ansatzes einer Didaktik für inklusive Lerngruppen: die Akzeptanz aller Schülerinnen und Schüler in ihrer Individualität, der Einsatz förderdiagnostisch fundierter individualisierter Curricula, die Verwirklichung eines adaptiven und binnendifferenzierten Unterrichts, eine besondere Aufmerksamkeit für die Herstellung von Gemeinsamkeit aller Schüler und die didaktische Umsetzung dieser Aspekte im Co-Teaching [...]. Anhand der Ergebnisse einer Interview-Studie mit Experten aus der Praxis wird dieser Ansatz in einem zweiten Schritt auf Praxisrelevanz überprüft und reflektiert.
Keywords: Inklusion; Didaktik; Unterricht; Co-Teaching; Individualisierung; Soziale Integration; Einstellungen

Culture’s Impact on Customer Motivation to Engage in Professional Service Enactments. - Schumann, Jan H; Wünderlich, Nancy; Zimmer, Marcus S (Schmalenbach Business Review)
Although professional service providers increasingly deliver their services globally, little is known about cross-cultural differences in customers’ motivation to participate in service production. To address this lacuna, we survey a total of 2,284 banking customers in 11 countries on their motivation to provide personal information to, and follow the advice of, their service providers. We find differences in both aspects, but only the differences in providing personal information can be explained by the cultural values of uncertainty avoidance, individualism/collectivism, and masculinity/femininity. To perform certain tasks in the service process, global professional service providers should acknowledge cultural differences in customers’ motivations.
Keywords: Co-Production; Culture; Customer Participation; Professional Services

A Formal Behavioral Semantics for TestML - Großmann, Jürgen; Müller, Wolfgang (Proc. of ISOLA 06)
TestML is an XML-based language for the exchange of test descriptions in automotive systems design and mainly introduced through the structural definition of an XML schema as an independent exchange format for existing tools and methods covering a wide range of different test technologies. In this paper, we present a rigorous formal behavioral semantics for TestML by means of Abstract State Machines (ASMs). Our semantics is a concise, unambiguous, high-level specification for TestML-based implementations and serves as a basis to define exact and well-defined mappings between existing test languages and TestML.
Keywords: System testing; Software testing; Automotive engineering; Automatic testing; Machinery production industries; Protocols; Hardware design languages; Samarium; XML; Computer industry

System-level performance evaluation of reconfigurable processors - Enzler, Rolf; Plessl, Christian; Platzner, Marco (Microprocessors and Microsystems)
Reconfigurable architectures that tightly integrate a standard CPU core with a field-programmable hardware structure have recently been receiving impact of these design decisions on the overall system performance is a challenging task. In this paper, we first present a framework for the cycle-accurate performance evaluation of hybrid reconfigurable processors on the system level. Then, we discuss a reconfigurable processor for data-streaming applications, which attaches a coarse-grained reconfigurable unit to the coprocessor interface of a standard embedded CPU core. By means of a case study we evaluate the system-level impact of certain design features for the reconfigurable unit, such as multiple contexts, register replication, and hardware context scheduling. The results illustrate that a system-level evaluation framework is of paramount importance for studying the architectural trade-offs and optimizing design parameters for reconfigurable processors.
Keywords: FPGA; reconfigurable computing; co-simulation; Zippy

A UML Virtual Machine for Embedded Systems - Schattkowsky, Tim; Müller, Wolfgang (Proceedings of ISNG 05)
StateCharts are well accepted for embedded systems specification for various applications. However, for the specification of complex systems they have several limitations. In this article, we present a novel approach to efficiently execute an UML 2.0 subset for embedded real- time systems implementation with focus on hardware interrupts, software exceptions, and timeouts. We introduce a UML Virtual Machine, which directly executes sequence diagrams, which are embedded into hierarchically structured state transition diagrams. Whereas state diagrams are directly executed as Embedded State Machines (ESMs), sequence diagrams are translated into UVM Bytecode. The final UVM execution is performed by the interaction of the ESM and the Bytecode Interpreter. Due to our completely model- based approach, the UVM runtime kernel is easily adaptable and scalable to different scheduling and memory management strategies.
Keywords: UML; Executable Models; Hardware/Software Co-design; Virtual Machine; Embedded Systems

Co-simulation of a Hybrid Multi-Context Architecture - Enzler, Rolf; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))
Reconfigurable computing architectures aim to dynamically adapt their hardware to the application at hand. As research shows, the time it takes to reconfigure the hardware forms an overhead that can significantly impair the benefits of hardware customization. Multi-context devices are one promising approach to overcome the limitations posed by long reconfiguration times. In contrast to more traditional reconfigurable architectures, multi-context devices hold several configurations on-chip. On demand, the device can quickly switch to another context. In this paper we present a co-simulation environment to investigate design trade-offs for hybrid multi-context architectures. Our architectural model comprises a reconfigurable unit closely coupled to a CPU core. As a case study, we discuss the implementation of a FIR filter partitioned into several contexts. We outline the mapping process and present simulation results for single- and multi-context reconfigurable units coupled with both embedded and high-end CPUs.
Keywords: Zippy; co-simulation